The Path to Resolving the Ethical Dilemma of Gene Editing Technology and Strategies for Enhancing Social Acceptance - Li, Mingqing (International Journal of Social Sciences and Public Administration, 2026)
The gene editing technology mediated by CRISPR-Cas9 has achieved breakthrough development and has great potential for application in the treatment of genetic diseases, optimization of agricultural breeding, and prevention and control of infectious diseases. However, the application of technology is not synchronized with ethical norms, causing multidimensional controversies. The current core ethical dilemmas focus on three aspects: at the technical level, off target risks and chimeric effects are not fully controllable, posing potential threats to the health of receptors; On an ethical level, reproductive cell editing may disrupt the integrity of the human gene pool, which is a core concern of the international scientific community; At the societal level, the high cost of technology leads to an imbalance in resource allocation, giving rise to issues of genetic discrimination and fairness, which have already begun to emerge in high-value gene therapy. The "He Jiankui Incident" in 2018 was a typical public case that exposed the shortcomings of ethical review and regulatory lag, widening the gap between technological development and social acceptance. This article analyzes ethical governance practices at home and abroad through literature research, combined with policy texts and public awareness survey data, to analyze the causes of difficulties and propose solutions from institutional construction, technical standards, and public communication. Research has shown that building a collaborative governance system of "government academia public" is the key to breaking through the impasse; Through transparent information dissemination, participatory decision-making, and regular ethical education, it is possible to effectively alleviate public uncertainty and gradually increase acceptance. This article provides theoretical support for the ethical application of technology and practical reference for the formulation of relevant policies.